P-024 Prominent Condylar Veins Causing Pulsatile Tinnitus: Dynamic Angiographic Confirmation. (29th July 2016) - Alexander, M; Meisel, K; Halbach, V; Darflinger, R; Nicholson, A; Settecase, F; Cooke, D; Higashida, R; Dowd, C; Hetts, S; Amans, M
Abstract : Introduction/purpose: Numerous processes can cause pulsatile tinnitus (PT), some of which are potentially life threatening. This case series describes a cause of PT – prominent condylar veins – that has undergone little investigation to date. This report characterizes angiographic findings in patients with prominent condylar veins and means to localize symptoms to these structures using dynamic angiography with head positioning and venous balloon test occlusion. Materials and methods: Retrospective analysis was performed under IRB approved protocol for 43 consecutive PT patients referred for diagnostic angiography at a major academic medical center between January 2013 and December 2015. Rates of different etiologies of PT among patients in this group were noted. In addition to standard diagnostic cervicocerebral angiography, dynamic angiography with head turning was conducted. The effects of provocative maneuvers were measured using time-resolved flow analysis known (iFlow, Siemens Healthcare, Erlangen Germany). Results: 5 (11.6%) patients were found to have prominent condylar veins. 16 (37.2%) had a dAVF, 4 (9.3%) had a venous diverticulum, and 9 (20.9%) had no angiographic abnormality detected. The findings of the five patients with prominent condylar veins are summarized in the table . Representative images are provided in the figure . Conclusion: Prominent flow in condylar veins should be considered among the numerous causes of PT. This may be a frequent cause of these symptoms in patients who previously would have had no identifiable cause Further investigation is warranted with respect to this cause of PT and PT in general. Disclosures: M. Alexander: None. K. Meisel: None. V. Halbach: None. R. Darflinger: None. A. Nicholson: None. F. Settecase: None. D. Cooke: None. R. Higashida: None. C. Dowd: None. S. Hetts: None. M. Amans: None.